Biomarkers responses and contaminant levels in fin whale (Balaenoptera physalus) skin biopsies of the pelagos sanctuary in the gulf of California (Mexico) - FOSSI, MARIA CRISTINA; Urban J.; CASINI, SILVIA; Maltese S.; SPINSANTI, GIACOMO; Panti C.; Porcelloni S.; Panigada S.; Lauriano G.; Niño C.; Rojas Bracho L.; Jimenez B.; et al. (2009)
The main objective of this study was to apply a suite of sensitive non-lethal biomarkers in skin biopsy of fin whales (Balaenoptera physalus) to evaluate the toxicological status of this mysticete in the Pelagos sanctuary (Mediterranean Sea) and in the Gulf of California (Sea of Cortez-Mexico). We developed a “multi-trialbiomarker- tool”, combining molecular biomarkers (western blot of CYP1A1, CYP2B) and gene expression (qRT-PCR of HSP70, ER, AhR, E2F-1) with analysis of OCs, PAHs and PBDEs. In the first phase we explored the level and the effects of OCs, PBDEs and PAHs in skin biopsies of fin whales of the two populations. In the second (in vitro) phase we applied this approach to whale biopsy slices treated with mixtures of OCs and PBDEs in order to explore the toxicological effects of these contaminants. The multi-trial biomarker tool applied to skin biopsies underlined differences in OCs, OCs-EDCs, PBDEs, PAH levels and molecular and gene expression biomarker responses between the two populations, revealing a higher toxicological stress in the Mediterranean fin whales. Of particular concern were the high levels of low brominated PBDEs found in the Mexican whale specimens.